Tata Kelola Pasar Tradisional dan Pendapatan Pedagang setelah Adanya Revitalisasi Pasar (Studi Kasus Pasar Kapal Kecamatan Mengwi Kabupaten Badung) - CAHYANI, NOVIA MILA; SUAMBA, I KETUT; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022DO - 10.24843/JAA.2022.v11.i01.p28, 2022)
Traditional Market Management and Trader Income After Revitalization  (Case Study of Kapal Traditional Market in Mengwi District, Badung Regency).  The existence of traditional markets is increasingly displaced by the expansion of supermarkets. This is due to the physical conditions of traditional markets which seem dirty and smelly. The cause is the lack of good market management by traditional market managers. One way to maintain the existence of traditional markets is market revitalization. Revitalization helps to improve the physical condition of the market. Moreover, Standard Operating Procedures (SOP) is also necessary. Good market management may help to improve the income of traders. This study aims to identify income of traders and the management of Kapal Traditional Market after revitalization. The data used are primary data that was obtain by distributing questionnaires to 16 traders of agricultural products in the Market. Secondary data was obtained from related literature. The results show that the management of the Kapal Traditional Market has been running according to the SOP and the highest average income is obtained by fruit traders, amounting to Rp 34.687.166 for one year or Rp 2.890.597 for one month. However, the income is below the average net income for self-employment according to BPS, which is Rp 3,000,400 for one month. The manager of the traditional market should consider social media promotion in order to increase the income of the traders.